1998
DOI: 10.1063/1.121285
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of electron and hole leakage in 1.3 μm AlGaInAs/InP quantum well lasers using multiquantum barrier

Abstract: The slope efficiency and threshold current density of 1.3 μm AlGaInAs/InP lasers with AlInAs–AlGaInAs multiquantum barrier (MQB) are experimentally studied and compared with the conventional step-index separate confinement heterostructure (SCH) laser. With the MQBs at the guiding layers, the characteristic temperature can be improved as much as 10 K as compared with the conventional SCH laser. This is attributed to the suppression of electron and hole leakage currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…GaAs-A1As Distributed Bragg Reflectors are necessary for VCSELs [8] and resonant cavity-enhanced photodetectors. The best values of To reported for InP-based 1.3 pm lasers are about 60-70 K and the best values of the threshold current density are about 300-400 A/cm2 [9].…”
Section: Emission Lasermentioning
confidence: 98%
See 1 more Smart Citation
“…GaAs-A1As Distributed Bragg Reflectors are necessary for VCSELs [8] and resonant cavity-enhanced photodetectors. The best values of To reported for InP-based 1.3 pm lasers are about 60-70 K and the best values of the threshold current density are about 300-400 A/cm2 [9].…”
Section: Emission Lasermentioning
confidence: 98%
“…Recently, using an approach of stacked 1.3 pm-emitting QDs, GaAs-based lasers [ 101 with threshold current density of 65 A/cm2 (four-side cleaved geometry) have been grown using MBE, a value much lower than previously reported [9]. Ground state lasing near 1.3 pm (see Fig.…”
Section: Emission Lasermentioning
confidence: 99%
“…Moreover, in AlGaInAs/InP, it is easier than in GaInAsP/InP to change the band gap ∆E g while maintaining the same strain in the quantum well. Our laser structures differ from conventional MBE-grown high temperature AlGaInAsbased laser structures, 16,18 as our structures contain InP cladding layers. It is therefore surprising that in spite of all these potential advantages of AlGaInAs over GaInAsP, the 1.3 µm AlGaInAs/InP lasers have been studied relatively little in the literature.…”
Section: Introductionmentioning
confidence: 94%
“…2 Enhanced carrier confinement translates into a reduction in N b by a factor of ~e 2 (about an order of magnitude) at room temperature, suggesting smaller 981 AlGaInAs/InP Strained-Layer Quantum Well Lasers at 1.3 µm Grown by Solid Source Molecular Beam Epitaxy temperature sensitivity of external quantum efficiency and better T 0 . 2,[12][13][14][15][16][17] In the present paper, 1.3 µm AlGaInAs/InP quantum well lasers have been prepared and the material quality and performance characteristics of the lasers have been examined. This is accomplished just by interchanging Ga and Al, due to the small difference (0.12%) in the lattice constants of GaAs and AlAs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Takemasa et al 15 verified this theory experimentally. Irikawa et al 16 and subsequent investigations 17,18 analyzed the effect of AlInAs/ AlGaInAs multiple quantum barriers and showed that these LDs have superior electrical characteristics of lower threshold current density Jth and higher characteristic temperature T 0 than those without multiple quantum barriers. Nevertheless, the Al composition and thickness of multiple quantum barriers should be accurately controlled.…”
Section: Introductionmentioning
confidence: 98%